The impact of social networks on youth health during the isolation period: an integrative review (Research, Society and Development, 2021)
Objective: To identify through the literature the impact of social networks on the mental health of young people during isolation in the pandemic of COVID-19 and describe the ways found to reduce the risks presented. Method: This is an integrative literature review, using the databases: LILACS, MEDLINE, IBECS, BDENF / Virtual Health Library, using the keywords Social network, Mental health, COVID and young people, published between 2019 and 2021. Results: Twelve articles were found that answered the research question. The analysis resulted in three categories: the harmful effects on the mental health of young people, the use and impact of social networks and ways to alleviate the problem. Final considerations: The impacts arising from social isolation and social networks are noticeable and have a long term duration, the vast majority of young people have severe mental disorders and it is necessary to combat this problem, the support of parents and the health system.